PhD student-supervisor relationship and its impacts: a perspective of the interpersonal relationship model - Li, Yingxiu; Xu, Wendan; Chen, Junjun (Frontiers in Education, 2025)
IntroductionThis study aimed to explore the PhD student-supervisor relationship and its impacts on students and supervisors from a qualitative perspective.MethodsA total of 50 PhD students and 11 supervisors from Hong Kong were approached using focus groups and individual interviews. Based on the interpersonal relationship model, this study conducted interviews with students to examine their perceptions of eight styles of relationships and their impact on students.ResultsThe results highlighted that the PhD student-supervisor relationship affected student academic achievement, well-being, and career and social network development. The interviews with the supervisors showed the impact on supervisors related to well-being, reflection on coaching style, and selection for future students.DiscussionFindings provide theoretical insights and conceptual and practical implications for understanding the eight styles of PhD student-supervisor relationships. This study also offers recommendations on university policies aiming to enhance the PhD student-supervisor relationship in order to boost positive impacts and hinder negative impacts.